Current concepts in genetics of nonsyndromic clefts - Murthy Jyotsna; Bhaskar LVKS (Indian Journal of Plastic Surgery)
Nonsyndromic cleft lip and palate is a complex genetic disorder with variable phenotype, largely attributed to the interactions of the environment and multiple genes, each potentially having certain effects. Numerous genes have been reported in studies demonstrating associations and/or linkage of the cleft lip and palate phenotypes to alleles of microsatellite markers and single nucleotide polymorphisms within specific genes that regulate transcription factors, growth factors, cell signalling and detoxification metabolisms. Although the studies reporting these observations are compelling, most of them lack statistical power. This review compiles the evidence that supports linkage and associations to the various genetic loci and candidate genes. Whereas significant progress has been made in the field of cleft lip and palate genetics in the past decade, the role of the genes and genetic variations within the numerous candidate genes that have been found to associate with the expression of the orofacial cleft phenotype remain to be determined.